The complete mitochondrial genome of Paramesotriton chinensis (Caudata: Salamandridae) and phylogenetic studies of Paramesotriton. Issue 1 (1st January 2017) - Yang, Jia; Yu, Lipeng; Zhang, Shuyan; Liu, Rilin; Chen, Cangsong; Lin, Hung-Du
Abstract: The complete mitochondrial genome of the Asian warty newt Paramesotriton chinensis was sequenced. The complete mitogenome of P. chinensis is a circular double-stranded DNA sequence that is 16, 361 bp long and was biased toward A + T content at 61.3% (33.0% A, 28.3% T, 23.9% C, and 14.7% G). The complete mitogenome of P. chinensis consists of 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), 1 ribosomal RNAs (16S rRNA), and 1 putative control region. This study presented the complete mitogenome of P. chinensis and provided essential and important DNA molecular data for further phylogenetic and evolutionary analysis for genus Paramesotriton .